2010
DOI: 10.1037/a0018287
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in executive function and central coherence predict developmental changes in theory of mind in autism.

Abstract: There is strong evidence to suggest that individuals with autism show atypicalities in multiple cognitive domains, including theory of mind (ToM), executive function (EF), and central coherence (CC). In this study, the longitudinal relationships among these 3 aspects of cognition in autism were investigated. Thirty-seven cognitively able children with an autism spectrum condition were assessed on tests targeting ToM (false-belief prediction), EF (planning ability, cognitive flexibility, and inhibitory control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
174
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 213 publications
(195 citation statements)
references
References 102 publications
14
174
1
6
Order By: Relevance
“…Differences in scale alone might be one reason for the discrepancy between the inefficiencies reported here and the previous reports of heightened performance on small-scale visual search tasks (3)(4)(5), and future experiments will need to assess directly this possibility. We suggest, however, that the disadvantage for foraging is most likely directly attributable to the cognitive profile of autism (25,26) (unrelated to systemizing), which now appears to be wellsuited to table-top or computerized visual search but not to search in a wider context such as the foraging space. To forage successfully, participants must be able to orientate themselves effectively in space and to remember where they searched previously within the space; neither of these skills are required in classic small-scale visual search paradigms (14).…”
Section: Discussionmentioning
confidence: 98%
“…Differences in scale alone might be one reason for the discrepancy between the inefficiencies reported here and the previous reports of heightened performance on small-scale visual search tasks (3)(4)(5), and future experiments will need to assess directly this possibility. We suggest, however, that the disadvantage for foraging is most likely directly attributable to the cognitive profile of autism (25,26) (unrelated to systemizing), which now appears to be wellsuited to table-top or computerized visual search but not to search in a wider context such as the foraging space. To forage successfully, participants must be able to orientate themselves effectively in space and to remember where they searched previously within the space; neither of these skills are required in classic small-scale visual search paradigms (14).…”
Section: Discussionmentioning
confidence: 98%
“…Recent research indicates that false-belief performance in ASD may be predicted by executive function (Pellicano, 2010) and syntactic language skills (Paynter & Peterson, 2010). It is thus possible that the consistently poor performance of children with ASD on the FB and FS tasks reflects their impairments in executive function and language.…”
mentioning
confidence: 99%
“…Yet, others suggest executive functioning and the use of context, are better predictors (Pellicano 2010;Van Herwegen et al 2013). Although several studies have shown evidence for a deficit to use context in WS and ASD (for a review see Bernardino et al 2012 as well as HappĂ© and Frith 2006), studies in ASD have shown that this cannot explain performance on ToM tasks (Burnette et al 2005;HappĂ© 1997 One reason why the current theories cannot describe the difficulties observed in ASD and WS is that they only focus on domain-specific areas of cognition to explain ToM deficits.…”
Section: Introductionmentioning
confidence: 99%